THE EFFECTIVENESS OF INTERACTIVE METHODS IN TEACHING UZBEK TO FOREIGN STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the effectiveness of interactive teaching methods in the instruction of the Uzbek language to foreign students. With the increasing number of international students in Uzbekistan and the growing global interest in the Uzbek language, there is a need to modernize and optimize teaching approaches. The study highlights how interactive methods such as role-playing, gamification, dialogue modeling, multimedia presentations, and digital platforms contribute to enhanced language acquisition, learner engagement, and communicative competence. Through a comparative analysis of traditional and interactive pedagogical strategies, the research explores how these approaches can foster motivation, improve retention, and support the development of practical language skills. The article also addresses challenges encountered by educators and learners in implementing these methods and offers recommendations for curriculum improvement. The findings are relevant for philological institutions seeking to internationalize Uzbek language education and improve teaching efficacy.